Probing the origin of photoluminescence blinking in graphene nanoribbons: Influence of plasmonic field enhancement. (27th July 2020) - Lu, Mo; Pfeiffer, Markus; Senkovskiy, Boris V; Haberer, Danny; Hertel, Dirk; Meerholz, Klaus; Fischer, Felix R; Ando, Yoichi; Grüneis, Alexander; Lindfors, Klas
Abstract: The photoluminescence from aligned 7-atom wide armchair-edge graphene nanoribbons coupled to plasmonic nanoantennas was recently observed to display blinking. Photoluminescence blinking is a hallmark of emission from single quantum emitters. Here we explore the origin of the blinking. We study the influence of the local field enhancement in the vicinity of nanoantennas on the photoluminescence blinking. We observe a clear correlation between the blinking amplitudes and the plasmonic enhancement. For non-resonant metal nanostructures the blinking vanishes almost completely. Our results allow us to conclude that the blinking is an intrinsic feature of the emission from the graphene nanoribbons. This is in contrast to the case of single-molecule surface-enhanced Raman scattering, where it is known that ballistic charge transfer between plasmonic nanoparticles and the molecule under study critically contributes to the blinking.